Developing Indigenous Knowledge-Based Products to Improve Community Management Efficiency in Ban Thung Nang Khruan, Cha lae Sub-District, Thong Pha Phum District Kanchanaburi Province - Chaichana, Nobparat (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This objectives of this research were to: 1) explore the potential of community products in Ban Thung Nang Khruan, 2) develop prototype community products in Ban Thung Nang Khruan, and 3) identify product management approaches that aligned with the local way of life and market demands by utilizing local wisdom. The research area was Ban Thung Nang Khruan, Chalerm Subdistrict, Thong Pha Phum District, Kanchanaburi Province. A qualitative research methodology was employed for incorporating anthropological research methods and participatory research approaches. The sample group consisted of 24 participants including representatives from households, temples, and government agencies. Data were collected through interviews, observations, focus group discussions, and analyzed using content analysis and descriptive analysis. The research findings revealed that: 1) Ban Thung Nang Khruan had the potential to develop products that reflected local wisdom. Several community enterprised groups exist, each utilizing natural resources and traditional knowledge to create unique products. 2) The community had developed a prototype of woven textile products through the Ban Thung Nang Khruan handicraft group by integrating local wisdom with market demands. The product development process began with market trend analysis, consumer demand assessment, and product quality improvements based on the findings. As a result, the woven textiles produced are distinguished by their aesthetic appeal and durability, meeting customer expectations and achieving market competitiveness. 3) The approach to managing products based on local wisdom emphasized the use of natural resources and indigenous knowledge to create high-quality, unique products. This process was supported by building networks with external organizations and fostering collaboration among community members, enhancing the cultural value and uniqueness of the products. Furthermore, government agencies should provide support by establishing community product development learning centers and promoting online marketing to expand market opportunities.